The effects of microgravity on differentiation and cell growth in stem cells and cancer stem cells. (30th April 2020) - Grimm, Daniela; Wehland, Markus; Corydon, Thomas J.; Richter, Peter; Prasad, Binod; Bauer, Johann; Egli, Marcel; Kopp, Sascha; Lebert, Michael; Krüger, Marcus
Abstract: A spaceflight has enormous influence on the health of space voyagers due to the combined effects of microgravity and cosmic radiation. Known effects of microgravity (μ g ) on cells are changes in differentiation and growth. Considering the commercialization of spaceflight, future space exploration, and long-term manned flights, research focusing on differentiation and growth of stem cells and cancer cells exposed to real (r-) and simulated (s-) μ g is of high interest for regenerative medicine and cancer research. In this review, we focus on platforms to study r- and s-μ g as well as the impact of μ g on cancer stem cells in the field of gastrointestinal cancer, lung cancer, and osteosarcoma. Moreover, we review the current knowledge of different types of stem cells exposed to μ g conditions with regard to differentiation and engineering of cartilage, bone, vasculature, heart, skin, and liver constructs. : Abstract : Stem cells exposed to real or simulated microgravity show changes in growth and differentiation. The application of microgravity in cell biology represents a new technology used in the field of cancer research and translational regenerative medicine. It extends the current knowledge in the engineering of organoids, spheroids, or tissues (bone, liver, and heart among others) with and without scaffolds.